Ruthenium‐Catalyzed Hydrogenation of Oxygen‐Functionalized Aromatic Compounds in Water. Issue 11 (9th August 2013) - Jantke, Dominik; Cokoja, Mirza; Drees, Markus; Herrmann, Wolfgang A.; Kühn, Fritz E.
Abstract The application of a ruthenium complex, bearing a sulfonated bis‐N‐heterocyclic carbene (NHC) ligand as catalyst precursor for the hydrogenation of aromatic compounds is reported. The reaction proceeds under mild conditions in aqueous phase. The treatment of the Ru complex with 40 bar H2 at 60 °C in water (0.1 M KOH solution) leads to the formation of a catalytically active species, which can be stored and used in catalysis experiments. The catalyst is responsible for the hydrogenation of functionalized aromatic substrates exhibiting endo‐ and exo‐CO bonds, which are relevant products in biomass conversion. Acetophenone is quantitatively reduced to 1‐cyclohexyl ethanol with a selectivity of 100 %. Various other oxygen‐functionalized aromatic substrates were also hydrogenated in moderate to quantitative conversions. To elucidate the nature of the catalytically active species, NMR, UV/vis, and ESI‐MS experiments were undertaken, showing the presence of a mononuclear Ru hydride complex. TEM measurements of a sample of the catalyst solution did not indicate the presence of nanoparticles. Mechanistic investigations point towards a homogenous mechanism.